A human cell atlas of fetal gene expression - Cao, Junyue; O'Day, Diana R; Pliner, Hannah A; Kingsley, Paul D; Deng, Mei; Daza, Riza M; Zager, Michael A; Aldinger, Kimberly A; Blecher-Gonen, Ronnie; Zhang, Fan; Spielmann, Malte; Palis, James; et al. (Science (American Association for the Advancement of Science), 2020)
The gene expression program underlying the specification of human cell types is of fundamental interest. We generated human cell atlases of gene expression and chromatin accessibility in fetal tissues. For gene expression, we applied three-level combinatorial indexing to >110 samples representing 15 organs, ultimately profiling ~4 million single cells. We leveraged the literature and other atlases to identify and annotate hundreds of cell types and subtypes, both within and across tissues. Our analyses focused on organ-specific specializations of broadly distributed cell types (such as blood, endothelial, and epithelial), sites of fetal erythropoiesis (which notably included the adrenal gland), and integration with mouse developmental atlases (such as conserved specification of blood cells). These data represent a rich resource for the exploration of in vivo human gene expression in diverse tissues and cell types.